2020
DOI: 10.4236/fns.2020.119061
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effects of Berries on Listeria monocytogenes

Abstract: The purpose of this study was to first evaluate the antimicrobial effects of powder and extracts of berries (rose-hip, aronia, sea buckthorn and hawthorn) on the development of antibiotic-resistant L. monocitogenes. Listeria monocytogenes is considered one of the most important pathogens responsible for food-borne infection. Antimicrobial properties were evaluated using the standard Kirby-Bauer disk diffusion method. Bacterial inactivation networks were determined and compared, as well as the possibility of us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…According to presence or absence of inhibition zones and zone diameters we determined in vitro antimicrobial activity of sea buckthorn extracts and powders against the tested L. monocytogenes. In previous studies it has been found that sea buckthorn, rosehip, black chokeberry, and hawthorn have antimicrobial effects on pathogenic microorganisms (Efenberger-Szmechtyk et al, 2020;Sandulachi, et al, 2020;Shah et al, 2020;Efenberger-Szmechtyk et al, 2021). According to the data obtained (Table 1), we observed that H. rahmnoides has the most pronounced effect on L. monocytogenes, especially concentrated extract 1 and 2 followed by R. canina and grape marc of V. vinifera.…”
Section: Resultssupporting
confidence: 55%
“…According to presence or absence of inhibition zones and zone diameters we determined in vitro antimicrobial activity of sea buckthorn extracts and powders against the tested L. monocytogenes. In previous studies it has been found that sea buckthorn, rosehip, black chokeberry, and hawthorn have antimicrobial effects on pathogenic microorganisms (Efenberger-Szmechtyk et al, 2020;Sandulachi, et al, 2020;Shah et al, 2020;Efenberger-Szmechtyk et al, 2021). According to the data obtained (Table 1), we observed that H. rahmnoides has the most pronounced effect on L. monocytogenes, especially concentrated extract 1 and 2 followed by R. canina and grape marc of V. vinifera.…”
Section: Resultssupporting
confidence: 55%
“…It is known that the AA of fruits depends on their antioxidant activity [6,12,13,16,24,31]. Xiangqun Gao et al [37,38] investigated the antioxidant activity of sea buckthorn and found that it depends on the content of phenolic substances and ascorbic acid, as well as the content of carotenoids.…”
Section: Antimicrobial Activity Analysismentioning
confidence: 99%
“…Sea buckthorn is a relevant source of vitamins (the most important being vitamins C and E, but vitamins B 1 , B 2 and K and bioflavonoids are also present), macro and microelements (nitrogen, phosphorus, iron, manganese, boron, calcium, aluminium, silicon and others) and antioxidants (catechin, myricetin, quercetin, p-coumaric acid, caffeic acid, L-ascorbic acid and gallic acid) [1][2][3][4]. Currently, papers containing experimental data obtained by various international researchers supporting the consumption of sea buckthorn fruits as functional foods [5][6][7], the use of the fruit as therapeutic remedies [8][9][10] and their use as sources of natural antioxidants with antimicrobial properties by the food industry [11][12][13][14]. Sea buckthorn fruits have a great potential as antimicrobial compounds against microorganisms [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 shows the composition of individual polyphenols, identified in hydroethanolic berries and grape pomace extracts (HPLC method) [21,22].…”
Section: Journal Of Engineering Sciencementioning
confidence: 99%